Critical Algorithmic Mediation: Rethinking Cultural Transmission and Education in the Age of Artificial Intelligence - Fulgencio Sánchez-Vera (Societies, 2025)
This conceptual paper explores how artificial intelligence—particularly machine learning-based algorithmic systems—is reshaping cultural transmission and symbolic power in the digital age. It argues that algorithms operate as cultural agents, acquiring a form of operative agency that enables them to intervene in the production, circulation, and legitimation of meaning. Drawing on critical pedagogy, sociotechnical theory, and epistemological perspectives, the paper introduces an original framework: Critical Algorithmic Mediation (CAM). CAM conceptualizes algorithmic agency through three interrelated dimensions—structural, operational, and symbolic—providing a lens to analyze how algorithmic systems structure knowledge hierarchies and cultural experience. The article examines the historical role of media in cultural transmission, the epistemic effects of algorithmic infrastructures, and the emergence of algorithmic hegemony as a regime of symbolic power. In response, it advocates for a model of critical digital literacy that promotes algorithmic awareness, epistemic justice, and democratic engagement. By reframing education as a space for symbolic resistance and cultural reappropriation, this work contributes to rethinking digital literacy in societies increasingly governed by algorithmic infrastructures.